(untitled) (Editora Impacto Científico, 2025)
This article proposes a technical and pedagogical rupture between two types of automatism observed in firearms training: vicious automatism, resulting from rushed and unconscious repetition, and conscious automatism, built through deliberate, segmented practice guided by technical feedback. The popular concept of “muscle memory” is critically addressed and replaced with the scientifically accurate term: procedural memory. The article is grounded in motor neuroscience, applied psychopedagogy, and classical skill acquisition models, such as the learning stages of Fitts and Posner (1967) and Ericsson’s (1993) theory of deliberate practice. Field data were collected throughout 2024, during the observation of 50 students in Firearms and Shooting Instructor Training Courses at ProPoint – Center for Specialized Training, located in Coroados, São Paulo, Brazil. The findings show that students trained with a focus on conscious execution, technical verbalization, and progressive correction achieved superior performance in consistency, self-diagnosis, and stress response, when compared to peers who prioritized fluency through accelerated repetition. A focused case study over six consecutive days reinforces that the type of automatism being formed — not merely the volume of practice — is the decisive factor in achieving true accuracy in shooting. This work advocates for the institutional adoption of the Conscious Automatism model as a formal training doctrine. Technical gestures must be understood before they are automated. Repetition alone is not enough — it must be guided, analyzed, and corrected. Because in the field, it is the type of automatism that defines the outcome.